Analisis Dampak Pembelajaran Daring terhadap Kemandirian Belajar Siswa - Elsi Fitrianis; Nurul Izzah Yasmin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of online learning on students' learning independence at the secondary school level. The research is motivated by the significant shift in the education system due to the pandemic, which required students to adapt to technology-based distance learning. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, interviews, and documentation, supported by quantitative questionnaires from previous studies. The findings indicate that online learning has both positive and negative effects on students' learning independence. Positive impacts include increased student responsibility in completing assignments, ease of accessing learning materials anytime and anywhere, and enhanced parental involvement in supporting their children's learning at home. However, negative effects were also identified, such as students' tendency to engage excessively in gaming, reduced effectiveness of the learning process, and delays in task submission due to workload accumulation. Regression analysis results show a significant influence between online learning and learning independence, although the effect is moderate to low in some cases. Factors such as learning motivation, self-efficacy, and the support of the online learning environment play crucial roles in shaping student independence. The study recommends collaboration among government, schools, teachers, parents, and the wider community to improve the quality and quantity of online learning facilities, as well as more varied learning strategies to optimally support the development of students' learning independence.